2004
DOI: 10.3122/jabfm.17.2.96
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Frequent Emergency Room Use by Medicaid-Insured Children with Asthma: A Combined Quantitative and Qualitative Study

Abstract: Background: Medicaid-insured asthmatic children frequently use emergency rooms (ERs). The reasons are unclear and have predominantly been studied in inner-city populations.Methods: We used billing data and focus groups to clarify reasons for frequent ER use by Medicaidinsured children with asthma living in rural areas and 23 towns in Kansas.Results: High ER utilization was concentrated in a small percentage of provider practices and children with asthma. Parents expressed strong preference for primary care tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 14 publications
4
31
0
Order By: Relevance
“…Among the explanations are cultural differences about the perceived utility of preventive care, the 24 hour per day access of emergency rooms, and the perceptions of dissatisfaction due to poor communication, disrespect, and racial/ethnic discrimination by health care provider. [35][36][37][38][39][40][41] …”
Section: Health Care Utilization: Emergency Room Use and Immunizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the explanations are cultural differences about the perceived utility of preventive care, the 24 hour per day access of emergency rooms, and the perceptions of dissatisfaction due to poor communication, disrespect, and racial/ethnic discrimination by health care provider. [35][36][37][38][39][40][41] …”
Section: Health Care Utilization: Emergency Room Use and Immunizationsmentioning
confidence: 99%
“…Results from QOL studies not only have characterized the impact of an illness on the quality of life, but also the fundamental role that the family_s financial status plays on the quality of life. 37 Consequently, it is likely that QOL might identify differences in the quality of life between income groups, even though that is not their initial intent. But QOL are individual-level indicators.…”
Section: Individual-level Indicators (Quality Of Life)mentioning
confidence: 99%
“…This increased use of the ER is closely tied to reduced access to a regular source of care, especially primary care providers. Besides difficulties in obtaining urgent advice or appointments, parents frequently had difficulties in transport, childcare, or work release that impeded using the primary care office as the principal site of asthma care [13]. This mechanism could certainly be at play in our study, since less than 60% of patients at our city hospital received an US on the day of admission.…”
Section: Discussionmentioning
confidence: 67%
“…Medicaid beneficiaries make almost 20% of all ER visits and, in particular, Medicaid children are noted to have rising rates of ER use [12]. Fredrickson et al found that ER use was concentrated in a subgroup of children with half of all visits made by 17% of the Medicaid-insured children who used any emergency or hospital services for asthma [13]. This increased use of the ER is closely tied to reduced access to a regular source of care, especially primary care providers.…”
Section: Discussionmentioning
confidence: 97%
“…29,30 Zorc et al 31 found that organizational barriers to seeing PCP (such as lack of convenient appointments or prolonged waits in PCP office) were factors associated with follow-up after a pediatric ED visit for asthma.…”
Section: Discussionmentioning
confidence: 98%